2012
DOI: 10.5713/ajas.2012.12331
|View full text |Cite
|
Sign up to set email alerts
|

MHC-DQB1 Variation and Its Association with Resistance or Susceptibility to Cystic Echinococcosis in Chinese Merino Sheep

Abstract: Cystic echinococcosis (CE), one of the world’s most geographically widespread diseases, still represents a considerable economic and public health significance, although a variety of methods has been used to control the disease. It has been demonstrated that genetic factors, especially variations in MHC loci, can influence the outcome of CE infection in the human population. The study described here was designed to determine whether variation in MHC-DQB1 was associated with susceptibility or resistance to CE i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…Previously, we carried out a series of studies to research the relationship between MHC polymorphisms and resistance or susceptibility to CE in native Chinese sheep, including Chinese Merino [ 21 ], Duolang [ 28 ], and Kazakh sheep [ 29 ]. Our previous studies indicated that in Kazakh sheep, when exposed to the same number of parasites, the rate of E. granulosus infection in the internal organs of sheep with haplotype MHC Mva I bc- Sac II ab- Hin 1I ab haplotype was significantly lower than in sheep without this haplotype.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previously, we carried out a series of studies to research the relationship between MHC polymorphisms and resistance or susceptibility to CE in native Chinese sheep, including Chinese Merino [ 21 ], Duolang [ 28 ], and Kazakh sheep [ 29 ]. Our previous studies indicated that in Kazakh sheep, when exposed to the same number of parasites, the rate of E. granulosus infection in the internal organs of sheep with haplotype MHC Mva I bc- Sac II ab- Hin 1I ab haplotype was significantly lower than in sheep without this haplotype.…”
Section: Introductionmentioning
confidence: 99%
“…It has been found that when sheep were infected with oncospheres (larvae of E. granulosus ), the small intestine tissue was the first mucosal immune barrier that must be passed through, where various antibodies, cytokines, and other immune molecules are expressed in response to exogenous stimuli [ 12 ]. These molecules could be involved in stopping larval growth of E. granulosus at the very first stages [ 11 , 21 , 28 , 29 ]. Hence, we were interested to see the molecular mechanisms of CE resistance in Kazakh sheep with the resistant haplotype, at the very first stage of infection.…”
Section: Introductionmentioning
confidence: 99%